AVALIAÇÃO E PROPOSTAS DE MITIGAÇÃO DE ATROPELAMENTOS DA FAUNA SILVESTRE NO TRECHO DA RODOVIA BR-469, NO PARQUE NACIONAL DO IGUAÇU/PR, PATRIMÔNIO NATURAL MUNDIAL - Silva, Bruna Vianna Garcia da (2025)
The BR-469 highway, which crosses the interior of Iguaçu National Park (PNI), poses a significant threat to local wildlife, especially due to the increasing number of roadkill incidents recorded between 2016 and 2023. This study aimed to identify the most vulnerable taxonomic groups, analyze the relationship between roadkill frequency and traffic intensity, and map key hotspots along the 11.6 km stretch of road within the protected area. Only records with adequate spatial and taxonomic precision were considered, totaling 630 occurrences documented through systematic weekly monitoring. Data analysis was performed using Generalized Linear Models (GLMs) with Poisson distribution, considering traffic intensity, road sinuosity, proximity to water bodies, vegetation structure along the road, and seasonality as explanatory variables. Faunal records were grouped into five categories: mammals, birds, reptiles, amphibians, and gastropods. Results indicated that amphibians, gastropods (especially Megalobulimus sanctipauli), and reptiles were the most frequently affected, particularly in sections close to aquatic habitats and dense vegetation. Although mammals and birds were less affected numerically, a positive correlation with increased traffic was also observed. The distribution of incidents was not homogeneous, with well-defined peaks indicating wildlife mortality hotspots. These patterns highlight the influence of landscape structure and road use intensity on fauna mortality. Based on these findings, the implementation of mitigation measures is recommended, including wildlife underpasses, guiding fences, targeted signage, and environmental education initiatives. Such strategies are essential to reduce the negative impacts on the park’s biodiversity and to promote coexistence between wildlife conservation and public road use.